Eudendrium undetermined - Peña Cantero, Álvaro L. (Zenodo, 2021)
Eudendrium sp. (*) Eudendrium sp. — Peña Cantero, 2009: 1745–1746, fig. 2a. Remarks. Peña Cantero (2009) found this hydroid off Young Island, at depths between 103 and 127 m, and with gonophores in March, indicating that the material was allied with Eudendrium cyathiferum Jäderholm, 1904, but that it was necessary to know the cnidome of Jäderholm's species to settle the issue. : Published as part of Peña Cantero, Álvaro L., 2021, Additions to knowledge of the biodiversity of benthic hydroids (Cnidaria: Hydrozoa) in the Balleny Islands (Antarctica), pp. 321-336 in Zootaxa 4966 (3) on page 323, DOI: 10.11646/zootaxa.4966.3.4, http://zenodo.org/record/4736691 : {"references": ["Pena Cantero, A. L. (2009) Benthic hydroids (Cnidaria, Hydrozoa) from the Balleny Islands (Antarctica). Polar Biology, 32, 1743 - 1751. https: // doi. org / 10.1007 / s 00300 - 009 - 0673 - 7", "Jaderholm, E. (1904) Mitteilungen ueber einige von der Schwedischen Antarctic Expedition 1901 - 1903 eingesammelte Hydroiden. Archives de Zoologie Experimentale et Generale, Series 4, 3 (Notes et revue 1), 1 - 14."]}